Analisis Peran E-commerce dalam Mendorong Pertumbuhan Ekonomi Digital di Indonesia - Muhammad Angka Widjaya; Muhammad Iqbal Fasa (Yayasan Literasi Sains Indonesia, 2025)
This ponder analyzes the part of e-commerce in driving advanced financial development in Indonesia. Within the setting of globalization and innovative progression, e-commerce has ended up a key division in transforming the national economy. Employing a mixed-method approach—literature audit, studies, and interviews—the inquire about uncovers that expanded e-commerce selection boosts efficiency, work creation, and commerce effectiveness. It too highlights shifts in customer behavior toward advanced exchanges and the rise of imaginative, universally versatile commerce models. Key enablers of this development incorporate strong IT framework, steady government arrangements, and rising advanced proficiency. The consider concludes that e-commerce not as it were quickens financial digitalization but moreover opens modern openings for diversification and progressed welfare. Down to earth proposals are advertised to assist policymakers and industry players reinforce computerized framework, improve human capital, and change controls to construct a more comprehensive and competitive computerized economy. This investigate points to educate methodologies for economical advanced financial advancement in Indonesia.